HELLO

Is there anyone who can help me with this question ? and thanks in advance …

I have a system of ODEs with initial conditions (first order) that is given bellow, but this system changes when the value of y(2) changes.

the initial conditions of the new system are the final values of the solutions of the previous system.

when y(2)<T_b, I have this sytem

%======================================

%y(2)< T_b

dydt(1) = A – B*y(1);

dydt(2) = (-a + b*y(1))*(y(2) – c) + d;

dydt(3) = 0;

%========================================

and when y(2)>=T_b the system becomes like this

%========================================

%y(2)>= T_b

dydt(1) = -C*(y(2)-T_b);

dydt(2) = D – E*y(2);

dydt(3) = G*(y(2)-T_b);

%=========================================

and when y(2) comes back under T_b (y(2)<T_b, the system becomes like this

%=========================================

%y(2)< T_b

dydt(1) = 0;

dydt(2) = h_1 – h_2*(y(2)-T_inf) -h_3*(y(2)-T_b);

dydt(3) = -K

%=========================================

## Best Answer